PENYELESAIAN SENGKETA BISNIS EKSPOR IMPOR TERHADAP WANPRESTASI PERJANJIAN JUAL BELI KOPI ANTARA KOPERASI PEDAGANG KOPI (KOPEPI) KETIARA DENGAN ROYAL COFFEE - Shapira, Kania; Anggraeni, Siti Wulan; Rossa, Reva Della; Chairunnisa, Chairunnisa; Fauziah, Alfiah Farhah; Wijaya, Mustika Mega (Jurnal Pahlawan, 2023)
The buying and selling process can be established by parties (sellers and buyers) from various countries, this can be referred to as international business. In the implementation of this international business process, an international agreement can be made, which is also known as an export-import agreement. So that it will cause legal consequences that bind the parties involved in the agreement. Legal consequences arise in the form of rights and obligations that must be fulfilled by the parties. As in the import-export agreement between the Ketiara Coffee Traders Cooperative (KOPEPI Ketiara) from Takengon, Central Aceh Regency with Royal Coffee from the United States. However, in its implementation there is a civil dispute in the form of default on the export-import agreement that has been made. The method used in this research report is normative law, with library approach techniques. The theories used in this research are agreement theory and effectiveness theory. The conclusion obtained in this research is that the exporter and importer continue to perform their obligations but not on time and the parties agree to resolve the dispute through non-litigation by negotiation. Keywords: Agreement, Default, Dispute Resolution, Sale and Purchase